Article 2. The Right to Non‑Discrimination”, in John Tobin, ed., *The UN Convention on the Rights of the Child: A Commentary - Besson, Samantha; Kleber, Eleonor (The UN Convention on the rights of the child: a commentary, 2019)
Comprehensive article-by-article analysis of the United Nations Convention on the Rights of the Child. Addresses a wide range of related issues including key interpretive questions. Contributions from specialist scholars in the field. Select bibliography at the end of each chapter directs readers to useful resources for further enquiry.